SISTEM INFORMASI ALUMNI PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS KRISTEN PETRA - Budhi Wijaya; Djoni Haryadi Setiabudi; Silvia Rostianingsih (Jurnal Infra, 2013)
Alumni Informatic department are increasing every year, so it need a tool to communicate each other. The website for alumni there is currently available only contains info such as www.kanitra.org dan sportfolio.petra.ac.id/alumni. Alumni do not have a feature to communicate with fellow alumni. Hence we need a website that has a good feature that can be used for alumni to communicate each other. This thesis begins with the process of creating web applications from design using flowchart and entity relationship diagram, after that proceed with the creating of an application using Hypertext Preprocessor (PHP) as a programming language and MySQL for its database. Features that will be made are member profile, job vacancy, advertisements, file sharing, search, chat, etc.Features that has been made is the member profile, news, events, job vacancy, chat, commercials, promos, file sharing, Facebook comment box. But some of these features have some drawbacks such as Facebook comment box could only share a comment on the user’s Facebook profile, can not comment on the group of alumni. But the website can send data such as news, event, ads, job vacancy to the Facebook group of alumni.